Governance of community forest areas in mainland Portugal over the last 40 years: results, current trends and future perspectives - Kolos, Iryna Skulska (2020)
Doutoramento em Engenharia Florestal e dos Recursos Naturais - Instituto Superior de Agronomia. Universidade de Lisboa